How We Shift Personalities While Speaking Different Languages - Saodat Sadikova; Anastasiya Nam (Genius Journals, 2022)
Whether language shapes our behavior has long been a contradicting issue. Several research into the connection between languages and the way we act was made over the course of decades. The current study discovered and recapitulated the last research on the effects of language use on personality perception and dialectical thinking, especially the Study 3 of the research, as it mainly concerns with the consequences of dialectical thinking on behavioral manifestations. In this study 68 participants demonstrated selfand other-perceived variations in personality and behavior across bilingual contexts.
Keywords: Perception; Dialectical Thinking; Shifts In Behavior; Behavioral Changeability